DEVELOPMENT OF TECHNICAL AND PHYSICAL FITNESS OF FEMALE STUDENTS THROUGH GAMES (Conferencea, 2023)
This article reflects the fact that the use of national and movement games to improve the technical and physical fitness of female students has led to a positive change in their level of technical and physical fitness in sports.